Full-spectrum solid-phase fluorescent material, synthetic method thereof and application of full-spectrum solid-phase fluorescent material in light-emitting diode

Through the solid-state reaction of urea, boric acid and phloroglucinol, the thermal domain heating method was used to solve the problem of aggregation-induced quenching of carbon dots in the solid state, achieving precise tuning and efficient preparation of full-color solid-state fluorescent materials, which is suitable for industrialization. application.

CN119331610AActive Publication Date: 2025-01-21QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411447302.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the prior art, carbon dots are prone to aggregation-induced quenching in solid films or powders, and it is difficult to achieve full-color solid-state luminescence, the preparation conditions are complex and the time is long, which is not conducive to industrial promotion.

Method used

By mixing urea, boric acid and phloroglucinol evenly and heating them to 200-250°C for solid-phase reaction, the thermal domain heating method is used to achieve precise control of the fluorescence emission wavelength only by adjusting the proportion of reactants.

Benefits of technology

The preparation of precisely tuned full-color solid-state fluorescent materials has been achieved, with long life, good stability, rapid and simple preparation process, and is suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331610A_ABST
    Figure CN119331610A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of advanced materials, and relates to a luminescent material, in particular to a full-spectrum solid-phase fluorescent material, a synthesis method thereof and application of the full-spectrum solid-phase fluorescent material in a light-emitting diode. The preparation method comprises the following steps: uniformly mixing urea, boric acid and phloroglucinol, then heating to 200-250 DEG C, and carrying out solid-phase reaction, thereby obtaining the product. Wherein the heating mode is heat domain heating. According to the solid-phase fluorescent material provided by the invention, accurate regulation and control of fluorescence emission wavelength can be realized only by adjusting the proportion of reactants, the prepared solid-phase fluorescent material is long in service life and good in stability and can be used for preparing a light-emitting diode, the preparation method is rapid and simple, and the reactants are cheap and easy to obtain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of advanced materials and relates to luminescent materials, in particular to a full-spectrum solid-phase fluorescent material and a synthesis method thereof and application thereof in light-emitting diodes. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] At present, the application of solid fluorescent materials based on carbon dots in light-emitting diodes, fingerprint recognition, biomedicine and other fields has attracted much attention. However, in solid films or powders, carbon dots often suffer from severe aggregation-induced quenching due to excessive fluorescence resonance energy transfer or direct π-π interactions, which limits the application of carbon dots in the solid-state field. In addition, in most cases, solid-state carbon dots exhibit single emission, but the field of luminescent display and lighting requires multi-color fluorescent materials as color converters. At the same time, most of the current colorful solid-state carbon dot synthesized with the help of external matrices. It is rare to achieve precise tuning of full-color solid-state luminescence of carbon dots without any external matrix.

[0004] According to the inventors, some researchers have used urea and phloroglucinol as raw reactants and water as solvent to obtain full-color solid fluorescent carbon dots through microwave one-step pyrolysis. However, the inventors further found that the full-color solid fluorescent carbon dots need to adjust the reactant ratio and microwave reaction power at the same time to achieve a certain degree of adjustment of the fluorescent color, and require more complicated subsequent treatment, complex preparation conditions, and long time, which is not conducive to industrial promotion. Summary of the invention

[0005] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a full-spectrum solid-phase fluorescent material, a synthesis method thereof, and an application thereof in light-emitting diodes. The solid-phase fluorescent material provided by the present invention can achieve precise control of the fluorescence emission wavelength only by adjusting the ratio of reactants, and the prepared solid-phase fluorescent material has a long life and good stability, and can be used for the preparation of light-emitting diodes. The preparation method is fast and simple, and the reactants are cheap and readily available.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, a method for synthesizing a full-spectrum solid-phase fluorescent material is provided, wherein urea, boric acid and phloroglucinol are uniformly mixed, and then heated to 200-250° C. for solid-phase reaction to obtain the material; wherein the heating method is thermal domain heating.

[0008] The hot zone heating described in the present invention refers to a method of first heating the heating medium and then collecting heat from the reaction system through the heating medium, such as water bath heating (the heating medium is water), oil bath heating (the heating medium is oil), air bath heating (the heating medium is air), etc. Among them, those skilled in the art can select a suitable hot zone heating method according to the target temperature of heating, such as air bath heating in the laboratory, heating jacket heating or oven heating, etc.

[0009] Based on the prior art described in the background technology, the present invention unexpectedly found that full-color solid fluorescent carbon dots can also be made by changing the heating method from microwave heating to hot zone heating (especially air bath heating such as oven heating), and the fluorescent color can be adjusted by only adjusting the ratio of reactants. The study found that after changing the heating method, the fluorescence intensity and fluorescence luminescence efficiency were both reduced, thus limiting its specific application.

[0010] In order to solve the problem of fluorescence intensity and reducing fluorescence luminescence efficiency, the present inventors unexpectedly discovered in further research that adding boric acid to the reactants on the basis of changing the heating method can not only ensure the acquisition of full-spectrum solid-phase fluorescent materials, but also significantly improve their fluorescence intensity and fluorescence luminescence efficiency.

[0011] Generally speaking, the reaction time of microwave heating is generally lower than that of other heating methods. However, the present invention unexpectedly discovered in the experiment that the reaction time of the synthesis method of changing the heating method provided by the present invention is as low as 6 minutes, that is, the reaction time is shorter and the safety factor is higher.

[0012] On the other hand, a full-spectrum carbon dot fluorescent material is obtained by the above synthesis method.

[0013] A third aspect is an application of the above-mentioned full-spectrum carbon dot fluorescent material in a light-emitting diode.

[0014] The beneficial effects of the present invention are:

[0015] (1) The present invention uses urea, boric acid and phloroglucinol for a one-step pyrolysis method to obtain a precisely tuned full-color solid fluorescent material. The preparation process is rapid, solvent-free, low in energy consumption, and low in pollution, solving the problems of long reaction time and complex preparation conditions in the preparation of full-color solid-phase fluorescent materials. The method for synthesizing solid-phase fluorescent materials using a one-step pyrolysis method is simple to operate, low in cost, highly practical, does not require the participation of any solvent, and is free from dependence on reaction solvents, and is suitable for mass production and industrial promotion.

[0016] (2) The present invention can obtain solid-phase fluorescent materials with different fluorescent colors by changing the ratio of urea, boric acid and phloroglucinol, and thus can be applied to the preparation of light-emitting diode devices with different colors.

[0017] (3) Experiments show that the maximum emission wavelength of the full-spectrum solid-phase fluorescent material prepared by the present invention can be finely adjusted in the range of 410-620nm with an amplitude of 10nm. It covers a wider spectral wavelength range and has more flexible wavelength tunability, which is more conducive to broadening the chromaticity of the light-emitting diode device prepared therefrom. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 It is a normalized fluorescence spectrum of the fluorescent carbon nanomaterial prepared in Examples 1-22 of the present invention;

[0020] Figure 2 This is a fluorescence spectrum of the solid fluorescent material prepared in Example 4 of the present invention, and the inset is an optical photograph of the solid fluorescent material under a 365nm ultraviolet lamp;

[0021] Figure 3 This is a fluorescence spectrum of the solid fluorescent material prepared in Example 8 of the present invention, and the inset is an optical photograph of the solid fluorescent material under a 365nm ultraviolet lamp;

[0022] Figure 4 This is a fluorescence spectrum of the solid fluorescent material prepared in Example 12 of the present invention, and the inset is an optical photograph of the solid fluorescent material under a 365nm ultraviolet lamp;

[0023] Figure 5 This is a fluorescence spectrum of the solid fluorescent material prepared in Example 16 of the present invention, and the inset is an optical photograph of the solid fluorescent material under a 365nm ultraviolet lamp;

[0024] Figure 6 This is a fluorescence spectrum of the solid fluorescent material prepared in Example 19 of the present invention, and the inset is an optical photograph of the solid fluorescent material under a 365nm ultraviolet lamp;

[0025] Figure 7 This is a fluorescence spectrum of the solid fluorescent material prepared in Example 22 of the present invention, and the inset is an optical photograph of the solid fluorescent material under a 365nm ultraviolet lamp;

[0026] Figure 8 The UV-visible absorption spectra of the solid fluorescent materials prepared in Examples 4, 8, 12, 16, 19 and 22 of the present invention;

[0027] Fig. 9 X-ray powder diffraction patterns of solid fluorescent materials prepared in Examples 4, 8, 12, 16, 19 and 22 of the present invention;

[0028] Fig.10 The luminescence result diagram of the LED device prepared in Example 23 of the present invention, a is the luminescence diagram of the LED device, and b is the chromaticity diagram;

[0029] Fig.11 The luminescence result diagram of the LED device prepared in Example 24 of the present invention, a is the luminescence diagram of the LED device, and b is the chromaticity diagram;

[0030] Fig.12 The luminescence result diagram of the LED device prepared in Example 25 of the present invention, a is the luminescence diagram of the LED device, and b is the chromaticity diagram;

[0031] Fig.13 The luminescence result diagram of the LED device prepared in Example 26 of the present invention, a is the luminescence diagram of the LED device, and b is the chromaticity diagram;

[0032] Fig.14 The luminescence result diagram of the LED device prepared in Example 27 of the present invention, a is the luminescence diagram of the LED device, and b is the chromaticity diagram;

[0033] Fig.15 The luminescence result diagram of the LED device prepared in Example 28 of the present invention, a is the luminescence diagram of the LED device, and b is the chromaticity diagram;

[0034] Fig.16 The fluorescence emission spectra of the solid fluorescent materials prepared in Comparative Example 1 and Example 8 of the present invention are shown. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0036] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0037] As introduced in the background technology, the technical solution in the prior art for preparing full-color solid-state fluorescent carbon dots using urea and pyrogallol as raw material reactants has the problems of complex preparation conditions and long preparation time. The present invention proposes a full-spectrum solid-phase fluorescent material and a synthesis method thereof and its application in light-emitting diodes.

[0038] A typical embodiment of the present invention provides a method for synthesizing a full-spectrum solid-phase fluorescent material, wherein urea, boric acid and phloroglucinol are uniformly mixed, and then heated to 200-250°C for solid-phase reaction to obtain the material; wherein the heating method is thermal domain heating.

[0039] Experiments show that the solid fluorescent material prepared by the present invention emits different fluorescent colors when excited by a 365nm ultraviolet lamp.

[0040] The solid phase reaction described in the present invention refers to a reaction in which a solid phase raw material is treated without adding a solvent.

[0041] In some embodiments, the thermal zone heating is air bath heating.

[0042] In some embodiments, the heat zone heating is oven heating. In experimental operation, oven heating can heat the reaction system more uniformly.

[0043] The solid phase reaction time is not less than 6 minutes. In some embodiments, the solid phase reaction time is 10 to 12 minutes.

[0044] In some embodiments, the molar ratio of boric acid, urea and phloroglucinol is 1:1.8-2.2:0.001-10, preferably 1:1.8-2.2:0.01-8.5.

[0045] In some embodiments, the method for uniformly mixing urea, boric acid and phloroglucinol is grinding. By grinding, the three raw materials can be better mixed uniformly without introducing a solvent, thereby improving the efficiency of the solid phase reaction.

[0046] Another embodiment of the present invention provides a full-spectrum carbon dot fluorescent material obtained by the above-mentioned synthesis method.

[0047] A third embodiment of the present invention provides an application of the above-mentioned full-spectrum carbon dot fluorescent material in a light-emitting diode.

[0048] In some embodiments, the light emitting diode is an LED lamp.

[0049] Specifically, the LED lamp includes an ultraviolet chip and the solid fluorescent material, and the solid fluorescent material is encapsulated on the ultraviolet chip. More specifically, the method can be: evenly mixing the solid fluorescent material with encapsulation glue, coating the mixed material on the ultraviolet chip, and curing.

[0050] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0051] Example 1

[0052] Weigh 0.4 g urea, 0.2 g boric acid and 0.004 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a solid-phase fluorescent material with an emission wavelength of 410 nm can be obtained.

[0053] Example 2

[0054] Weigh 0.4 g urea, 0.2 g boric acid and 0.0025 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a solid-phase fluorescent material with an emission wavelength of 420 nm can be obtained.

[0055] Example 3

[0056] Weigh 0.4 g urea, 0.2 g boric acid and 0.005 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a solid-phase fluorescent material with an emission wavelength of 430 nm can be obtained.

[0057] Example 4

[0058] Weigh 0.4 g urea, 0.2 g boric acid and 0.0084 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a solid-phase fluorescent material with an emission wavelength of 440 nm can be obtained.

[0059] Example 5

[0060] Weigh 0.4 g urea, 0.2 g boric acid and 0.0126 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a solid-phase fluorescent material with an emission wavelength of 450 nm can be obtained.

[0061] Example 6

[0062] Weigh 0.4 g urea, 0.2 g boric acid and 0.0294 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 °C oven for solid phase reaction, and after 10 minutes, a 460 nm solid phase fluorescent material can be obtained.

[0063] Example 7

[0064] Weigh 0.4 g urea, 0.2 g boric acid and 0.042 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 °C oven for solid phase reaction, and after 10 minutes, a 470 nm solid phase fluorescent material can be obtained.

[0065] Example 8

[0066] Weigh 0.4 g urea, 0.2 g boric acid and 0.05 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 °C oven for solid phase reaction, and after 10 minutes, a 480 nm solid phase fluorescent material can be obtained.

[0067] Example 9

[0068] Weigh 0.4 g urea, 0.2 g boric acid and 0.063 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 490 nm solid phase fluorescent material can be obtained.

[0069] Example 10

[0070] Weigh 0.4 g urea, 0.2 g boric acid and 0.084 g phloroglucinol, place them in a mortar, grind and mix thoroughly, transfer them to a 50 mL beaker, place them in a 240 °C oven for solid phase reaction, and after 10 minutes, a 500 nm solid phase fluorescent material can be obtained.

[0071] Embodiment 11

[0072] Weigh 0.4 g urea, 0.2 g boric acid and 0.1 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 °C oven for solid phase reaction, and after 10 minutes, a 510 nm solid phase fluorescent material can be obtained.

[0073] Example 12

[0074] Weigh 0.4 g urea, 0.2 g boric acid and 0.126 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 520 nm solid phase fluorescent material can be obtained.

[0075] Embodiment 13

[0076] Weigh 0.4 g urea, 0.2 g boric acid and 0.168 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 530 nm solid phase fluorescent material can be obtained.

[0077] Embodiment 14

[0078] Weigh 0.4 g urea, 0.2 g boric acid and 0.252 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 540 nm solid phase fluorescent material can be obtained.

[0079] Embodiment 15

[0080] Weigh 0.4 g urea, 0.2 g boric acid and 0.378 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 550 nm solid phase fluorescent material can be obtained.

[0081] Example 16

[0082] Weigh 0.4 g urea, 0.2 g boric acid and 0.63 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 560 nm solid phase fluorescent material can be obtained.

[0083] Embodiment 17

[0084] Weigh 0.4 g urea, 0.2 g boric acid and 0.714 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 570 nm solid phase fluorescent material can be obtained.

[0085] Embodiment 18

[0086] Weigh 0.4 g urea, 0.2 g boric acid and 0.84 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 580 nm solid phase fluorescent material can be obtained.

[0087] Embodiment 19

[0088] Weigh 0.4 g urea, 0.2 g boric acid and 1.01 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 °C oven for solid phase reaction, and after 10 minutes, a 590 nm solid phase fluorescent material can be obtained.

[0089] Embodiment 20

[0090] Weigh 0.4 g urea, 0.2 g boric acid and 1.26 g phloroglucinol, place them in a mortar, grind and mix thoroughly, transfer them to a 50 mL beaker, place them in a 240 °C oven for solid phase reaction, and after 10 minutes, a 600 nm solid phase fluorescent material can be obtained.

[0091] Embodiment 21

[0092] Weigh 0.4 g urea, 0.2 g boric acid and 1.5 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 ° C oven for solid phase reaction, and after 10 minutes, a 610 nm solid phase fluorescent material can be obtained.

[0093] Embodiment 22

[0094] Weigh 0.4 g urea, 0.2 g boric acid and 3.42 g phloroglucinol, place in a mortar, grind and mix thoroughly, transfer to a 50 mL beaker, place in a 240 °C oven for solid phase reaction, and after 10 minutes, a 620 nm solid phase fluorescent material can be obtained.

[0095] Embodiment 23

[0096] The LED device was prepared using the material obtained in Example 4. A UV LED chip with an emission wavelength of 365 nm was selected as a light pump, a certain amount of solid fluorescent material was uniformly mixed with organic silica gel and curing agent in a mass ratio of 1:4, and then an appropriate amount of the mixture was dripped onto the UV chip and dried at 100°C for 1 hour, and the LED device was prepared.

[0097] Embodiment 24

[0098] The LED device was prepared using the material obtained in Example 8. A UV LED chip with an emission wavelength of 365 nm was selected as a light pump, a certain amount of solid fluorescent material was uniformly mixed with organic silica gel and curing agent in a mass ratio of 1:4, and then an appropriate amount of the mixture was dripped onto the UV chip and dried at 100°C for 1 hour, and the LED device was prepared.

[0099] Embodiment 25

[0100] The LED device was prepared using the material obtained in Example 12. A UV LED chip with an emission wavelength of 365 nm was selected as a light pump, a certain amount of solid fluorescent material was uniformly mixed with organic silica gel and curing agent in a mass ratio of 1:4, and then an appropriate amount of the mixture was dripped onto the UV chip and dried at 100°C for 1 hour, and the LED device was prepared.

[0101] Embodiment 26

[0102] The LED device was prepared using the material obtained in Example 16. A UV LED chip with an emission wavelength of 365 nm was selected as a light pump, a certain amount of solid fluorescent material was uniformly mixed with organic silica gel and curing agent in a mass ratio of 1:4, and then an appropriate amount of the mixture was dripped onto the UV chip and dried at 100°C for 1 hour, and the LED device was prepared.

[0103] Embodiment 27

[0104] The LED device was prepared using the material obtained in Example 19. A UV LED chip with an emission wavelength of 365 nm was selected as a light pump, a certain amount of solid fluorescent material was uniformly mixed with organic silica gel and curing agent in a mass ratio of 1:4, and then an appropriate amount of the mixture was dripped onto the UV chip and dried at 100°C for 1 hour, and the LED device was prepared.

[0105] Embodiment 28

[0106] The LED device was prepared by mixing the materials obtained in Examples 12 and 22. A blue LED chip with an emission wavelength of 450 nm was selected as a light pump, a certain amount of solid fluorescent material was uniformly mixed with organic silica gel and curing agent in a mass ratio of 1:4, and then an appropriate amount of the mixture was dripped onto the ultraviolet chip and dried at 100°C for 1 hour, and the LED device was prepared.

[0107] like Figure 1 Shown is a normalized fluorescence spectrum of the solid fluorescent material prepared in Example 1-22, and the spectrum lines from left to right are the normalized fluorescence spectrum lines of the solid fluorescent material prepared in Example 1-22, indicating that the preparation method can accurately tune the CDs wavelength.

[0108] like Figure 2 The figure shows the fluorescence spectrum of the solid fluorescent material prepared in Example 4. The optimal excitation wavelength is at 382 nm, and the maximum emission peak is at 420 nm. The inset shows that the solid fluorescent material prepared in Example 4 emits blue fluorescence under a 365 nm ultraviolet lamp.

[0109] like Figure 3 The figure shows the fluorescence spectrum of the solid fluorescent material prepared in Example 8. The optimal excitation wavelength is at 417 nm, and the maximum emission peak is at 480 nm. The inset shows that the solid fluorescent material prepared in Example 8 emits blue-green fluorescence under a 365 nm ultraviolet lamp.

[0110] like Figure 4 The figure shows the fluorescence spectrum of the solid fluorescent material prepared in Example 12. The optimal excitation wavelength is at 467 nm, and the maximum emission peak is at 520 nm. The inset shows that the solid fluorescent material prepared in Example 12 emits green fluorescence under a 365 nm ultraviolet lamp.

[0111] like Figure 5 The figure shows the fluorescence spectrum of the solid fluorescent material prepared in Example 16. The optimal excitation wavelength is at 469 nm, and the maximum emission peak is at 560 nm. The inset shows that the solid fluorescent material prepared in Example 16 emits yellow fluorescence under a 365 nm ultraviolet lamp.

[0112] like Figure 6The figure shows the fluorescence spectrum of the solid fluorescent material prepared in Example 19. The optimal excitation wavelength is at 469 nm, and the maximum emission peak is at 590 nm. The inset shows that the solid fluorescent material prepared in Example 19 emits orange fluorescence under a 365 nm ultraviolet lamp.

[0113] like Figure 7 Shown is the fluorescence spectrum of the solid fluorescent material prepared in Example 22. The optimal excitation wavelength is at 468nm, the maximum emission peak is at 620nm, and the inset shows that the solid fluorescent material prepared in Example 22 emits red fluorescence under a 365nm ultraviolet lamp.

[0114] like Figure 8 Shown are the UV-visible absorption spectra of the solid fluorescent materials prepared in Examples 4, 8, 12, 16, 19, and 22, indicating that as the ratio of phloroglucinol to urea boric acid increases, the absorption peak of the solid fluorescent material continuously red-shifts.

[0115] like Fig. 9 Shown are the X-ray powder diffraction patterns of the solid fluorescent materials prepared in Examples 4, 8, 12, 16, 19, and 22, indicating the presence of a peak at around 23°.

[0116] like Fig.10 a shows the LED device prepared in Example 23, Fig.10 b is the corresponding chromaticity diagram, with coordinates (0.1614, 0.1223).

[0117] like Fig.11 a shows the LED device prepared in Example 24, Fig.11 b is the corresponding chromaticity diagram, with coordinates (0.1735, 0.241).

[0118] like Fig.12 a shows the LED device prepared in Example 25, Fig.12 b is the corresponding chromaticity diagram, coordinates (0.2988, 0.6202).

[0119] like Fig.13 a shows the LED device prepared in Example 26, Fig.13 b is the corresponding chromaticity diagram, with coordinates (0.4504, 0.4767).

[0120] like Fig.14 a shows the LED device prepared in Example 27, Fig.14 b is the corresponding chromaticity diagram, with coordinates (0.5031, 0.4767).

[0121] like Fig.15 a shows the LED device prepared in Example 28, Fig.15b is the corresponding chromaticity diagram, with coordinates (0.2768, 0.2936).

[0122] Comparative Example 1

[0123] Weigh 0.4 g of urea and 0.0084 g of phloroglucinol, place them in a mortar, grind and mix them thoroughly, transfer them to a 50 mL beaker, place them in a 240° C. oven for solid-phase reaction, and the solid-phase fluorescent material can be obtained after 10 minutes.

[0124] The fluorescence emission spectrum of the comparative example 1 and the fluorescence emission spectrum of the embodiment 4 are stacked as shown in FIG. Fig.16 As shown, the black spectrum line is the fluorescence spectrum line of the material of Example 4, with an emission wavelength of 440nm, and the red spectrum line is the fluorescence spectrum line of the material of Comparative Example 1, with an emission wavelength of 455nm, and by comparing the fluorescence intensity, it is found that the fluorescence intensity of Example 4 is stronger than that of Comparative Example 1. This proves that boric acid can significantly improve the fluorescence intensity of the material.

[0125] Comparative Example 2

[0126] Weigh 0.2 g of boric acid, 0.4 g of urea and 0.0073 g of resorcinol, with a molar ratio of boric acid, urea and resorcinol of 1:2:0.02, place them in a mortar, grind and mix them thoroughly, transfer them to a 50 mL beaker, and place them in a 240 °C oven for solid-phase reaction. After 10 minutes, the solid-phase luminescent material can be obtained.

[0127] Comparative Example 3

[0128] Weigh 0.2 g of boric acid, 0.4 g of urea and 0.0073 g of hydroquinone, with a molar ratio of boric acid, urea and hydroquinone of 1:2:0.02, place them in a mortar, grind and mix thoroughly, transfer them to a 50 mL beaker, and place them in a 240 ° C oven for solid phase reaction. After 10 minutes, the solid phase luminescent material can be obtained.

[0129] Comparative Example 4

[0130] Weigh 0.2 g of boric acid, 0.4 g of urea and 0.0073 g of catechol, with a molar ratio of boric acid, urea and catechol of 1:2:0.02, place them in a mortar, grind and mix thoroughly, transfer them to a 50 mL beaker, and place them in a 240 ° C oven for solid phase reaction. After 10 minutes, the solid phase luminescent material can be obtained.

[0131] Comparative Example 5

[0132] Weigh 0.2 g of boric acid, 0.64 g of guanidine hydrochloride and 0.0084 g of phloroglucinol, with a molar ratio of boric acid, guanidine hydrochloride and phloroglucinol of 1:2:0.02, place them in a mortar, grind and mix them thoroughly, transfer them to a 50 mL beaker, and place them in a 240 ° C oven for solid phase reaction. After 10 minutes, the solid phase luminescent material can be obtained.

[0133] Comparative Example 6

[0134] Weigh 0.2 g of boric acid, 0.45 g of methylamine hydrochloride and 0.0084 g of phloroglucinol, with a molar ratio of boric acid, methylamine hydrochloride and phloroglucinol of 1:2:0.02, place them in a mortar, grind and mix them thoroughly, transfer them to a 50 mL beaker, and place them in a 240 ° C oven for solid phase reaction. After 10 minutes, the solid phase luminescent material can be obtained.

[0135] Comparative Example 7

[0136] Weigh 0.2 g of boric acid, 0.54 g of ethylamine hydrochloride and 0.0084 g of phloroglucinol, with a molar ratio of boric acid, ethylamine hydrochloride and phloroglucinol of 1:2:0.02, place them in a mortar, grind and mix thoroughly, transfer them to a 50 mL beaker, and place them in a 240 ° C oven for solid phase reaction. After 10 minutes, the solid phase luminescent material can be obtained.

[0137] Comparative Example 8

[0138] Weigh 0.2 g of boric acid, 0.62 g of propylamine hydrochloride and 0.0084 g of phloroglucinol, with a molar ratio of boric acid, propylamine hydrochloride and phloroglucinol of 1:2:0.02, place them in a mortar, grind and mix thoroughly, transfer them to a 50 mL beaker, and place them in a 240 ° C oven for solid phase reaction. After 10 minutes, the solid phase luminescent material can be obtained.

[0139] Comparative Example 9

[0140] Weigh 0.2 g of boric acid, 0.86 g of ethylenediamine hydrochloride and 0.0084 g of phloroglucinol, with a molar ratio of boric acid, ethylenediamine hydrochloride and phloroglucinol of 1:2:0.02, place them in a mortar, grind and mix thoroughly, transfer them to a 50 mL beaker, place them in a 240 ° C oven for solid phase reaction, and the solid phase luminescent material can be obtained after 10 minutes.

[0141] As shown in Table 1, the present invention compares the fluorescence quantum yields of Example 1 and Comparative Examples 1-9, and finds that the solid-phase fluorescent materials synthesized from other phenolic and nitrogen-containing substances have low fluorescence luminescence efficiency and cannot synthesize full-spectrum solid-state fluorescent materials. This proves that phloroglucinol and urea cannot be replaced by other analogs.

[0142] Table 1 is a comparison of the fluorescence luminescence efficiency of the solid fluorescent materials prepared in Example 4 of the present invention and Comparative Examples 1-9

[0143]

[0144] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for synthesizing a full-spectrum solid-phase fluorescent material, characterized in that: The urea, boric acid and phloroglucinol are uniformly mixed, and then heated to 200-250° C. for solid phase reaction to obtain the product; wherein the heating method is hot zone heating.

2. The method for synthesizing a full-spectrum solid-phase fluorescent material as claimed in claim 1, characterized in that: The heat zone heating is air bath heating.

3. The method for synthesizing the full-spectrum solid-phase fluorescent material as claimed in claim 1, characterized in that: The heat zone heating is oven heating.

4. The method for synthesizing a full-spectrum solid-phase fluorescent material as claimed in claim 1, characterized in that: The solid phase reaction time is 10 to 12 minutes.

5. The method for synthesizing the full-spectrum solid-phase fluorescent material as claimed in claim 1, characterized in that: The molar ratio of boric acid, urea and phloroglucinol is 1:1.8-2.2:0.001-10, preferably 1:1.8-2.2:0.01-8.

5.

6. The method for synthesizing the full-spectrum solid-phase fluorescent material as claimed in claim 1, characterized in that: The method for uniformly mixing urea, boric acid and phloroglucinol is grinding.

7. A full-spectrum carbon dot fluorescent material, characterized in that: Obtained by the synthesis method according to any one of claims 1 to 6.

8. Use of the full-spectrum carbon dot fluorescent material according to claim 7 in a light-emitting diode.

9. The use according to claim 8, characterized in that: The light emitting diode is an LED lamp.

10. The use according to claim 9, characterized in that: The LED lamp comprises an ultraviolet light chip and the solid fluorescent material, and the solid fluorescent material is packaged on the ultraviolet light chip.

Citation Information

Patent Citations

  • Solid-state fluorescent carbon quantum dot with variable luminous color and preparation method thereof

    CN110589801A

  • Solid red light carbon dot based on amide solvent and preparation method of solid red light carbon dot

    CN114806557A

  • Method for producing carbon quantum dots

    US20240174922A1